2019
DOI: 10.1002/macp.201900439
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of 2D p–π Conjugated Polysquaraines for Both Fullerene and Nonfullerene Polymer Solar Cells

Abstract: So far, squaraine‐based polymer donors have been less explored for the bulk heterojunction (BHJ) polymer solar cells. In this work, two new p–π conjugated polysquaraines (PASQ‐BDT1 and PASQ‐BDT2) with different electron‐rich subunits on the squaraine skeleton are rationally developed as new polymer donors based on the 2D structure design concept. PASQ‐BDT2 with N,N‐diisobutylaniline subunits shows superior device performances in both fullerene and nonfullerene PSCs compared to PASQ‐BDT1 containing triphenylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…[ 81‐82 ] In addition, SQs also show a compatibility with non‐fullerene acceptors (NFAs). [ 83 ] In 2020, a BHJ OPD based on SQ:NFA blend film was successfully fabricated by Pecunia et al ., showing an appreciable D * of 4.70 × 10 11 Jones at 740 nm. [ 84 ] These results suggest that SQs may show greater potential for the development of high‐ performance NIR OPDs.…”
Section: Development Of Polymethine‐based Nir Opdsmentioning
confidence: 99%
“…[ 81‐82 ] In addition, SQs also show a compatibility with non‐fullerene acceptors (NFAs). [ 83 ] In 2020, a BHJ OPD based on SQ:NFA blend film was successfully fabricated by Pecunia et al ., showing an appreciable D * of 4.70 × 10 11 Jones at 740 nm. [ 84 ] These results suggest that SQs may show greater potential for the development of high‐ performance NIR OPDs.…”
Section: Development Of Polymethine‐based Nir Opdsmentioning
confidence: 99%
“…We then further developed two wide bandgap polysquaraines, i.e., SQ61 and SQ62, with suitable energy levels by using BDT as the copolymerization unit. [ 79 ] In both fullerene and nonfullerene OSCs, SQ62 showed superior device performance than that of SQ61 due to more favorable nanoscale morphology and enhanced hole mobility in the BHJ films. Moreover, it is demonstrated that solvent vapor annealing (SVA) played an effective role in improving the device performance by optimizing the BHJ morphology and increasing the hole mobility.…”
Section: Squaraine‐based Functional Materials For Photovoltaic Applicmentioning
confidence: 99%